Primary healthcare in island regions: A comprehensive analysis of trends, insights and future directions - Nur Rahmah; Amran Razak; Agus Bintara Birawida; Irwandy Irwandy (International Maritime Health)
BACKGROUND: Primary healthcare in island regions is a critical component of global health systems, yet it faces unique challenges due to geographical isolation, resource constraints and sociocultural factors. Aims: This study aimed to systematically analyze the global research landscape of primary healthcare in islands through a bibliometric analysis. MATERIAL AND METHODS: A comprehensive search was conducted to identify relevant publications using Scopus as the primary database. Keyword analysis, co-authorship networks and citation analysis were employed to explore research trends, collaboration patterns and influential authors and institutions. RESULTS: The results revealed a significant increase in research output over the past few decades, with the United States, Spain and Australia emerging as leading contributors. Key research themes included access to care, health workforce, chronic disease management and health promotion. Collaborative research networks were identified, particularly among researchers from island nations and developed countries. The analysis also highlighted the growing importance of digital health technologies in addressing the challenges of island healthcare. CONCLUSIONS: Research on island primary healthcare has grown steadily since 1972, with key contributions from the United States, Spain and Australia. Major themes include clinical care, health systems and policy. Trends evolved from clinical to systemic and demographic focuses, with future directions emphasizing digital technologies and participatory methods. These findings inform evidence-based policies to enhance island health services.